A pilot study of the efficacy of an adventure therapy programme on borderline personality disorder: A pragmatic controlled clinical trial. (11th February 2021) - Mendo‐Cullell, Mariona; Arenas‐Pijoan, Laura; Forné, Carles; Fernández‐Oñate, David; Ruiz de Cortázar‐Gracia, Natalia; Facal, Carmen; Torrent, Aurora; Palacios, Roberto; Pifarré, Josep; Batalla, Iolanda
Abstract: Adventure therapy (AT) is a therapeutic intervention that has demonstrated effectiveness in different populations, but there are no studies on this therapy in borderline personality disorder (BPD). The objective of this study was to assess the response to AT in comparison with treatment as usual (based on cognitive‐behavioural therapy) in patients with BPD. Regarding the comparison of the differences post‐therapy–pre‐therapy between both groups, some metabolic variables improved more in the AT group, with medium–large effect sizes. Almost all psychometric variables evolved better in the AT group, with negligible effects. AT could be considered in BPD treatment because it results in healthier lifestyle habits and increases functionality and quality of life in patients who are prone to self‐destruction. © 2021 John Wiley & Sons, Ltd. Highlights: Adventure therapy may be an effective treatment for borderline personality disorder. Adventure therapy may influence borderline patients to adopt healthier lifestyles. Adventure therapy has demonstrated a tendency to lower impulsivity and state anxiety. No decrease in autolytic risk was observed in this adventure therapy short‐term study. Adventure therapy improves functionality and quality of life in borderline patients.